2004
DOI: 10.1007/s10832-004-5112-0
|View full text |Cite
|
Sign up to set email alerts
|

Al2O3-MgO-ReOx (Re: Rare Earth)-Based LTCC and its Application to Multilayer Non-Shrinkage Substrate for Microwave Devices

Abstract: We studied the dielectric properties of Al 2 O 3 -MgO-ReO x (Re: rare earth) systems in the microwave region and found that the magnetoplumbite phases in the MgO-poor regions of MgReAl 11 O 19 (Re: La ∼ Tb) compositions had positive TCF (temperature coefficient of resonance frequency) values in spite of having low dielectric constants of under 20. By mixing a lead-free glass with the above system, a novel LTCC (which we term an AMSG) was obtained that was characterized by a low dielectric constant (<10), a nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…The low temperature co-fired ceramic (LTCC) technology has been extensively studied from its technical and commercial significance in the field of highly-integrated electronic components and modules [1][2][3][4]. The LTCC system generally consists of glass and ceramic.…”
Section: Introductionmentioning
confidence: 99%
“…The low temperature co-fired ceramic (LTCC) technology has been extensively studied from its technical and commercial significance in the field of highly-integrated electronic components and modules [1][2][3][4]. The LTCC system generally consists of glass and ceramic.…”
Section: Introductionmentioning
confidence: 99%
“…The samples were sintered at 900 • C in air for 4 h using free sintering (conventional sintering method) and restricted shrinkage sintering, respectively. Restricted shrinkage sintering is sintering the multilayer ceramic green body with no-shrinkage alumina substrate on both sides [10,11]. During firing, the multilayer ceramic in middle layer can be bonded by the sintered rigid board.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the ceramic green sheets shrink in the z direction, not in the x-y directions, due to the 0925-8388/$ -see front matter © 2008 Elsevier B.V. All rights reserved. doi:10.1016/j.jallcom.2008.02.049 constraining effects of the no-shrinkage alumina substrate layer [10,11]. The result of using restricted shrinkage sintering is obtaining the no camber and cracks multilayer composite samples, as are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The best dielectric properties, Qf = 72 000 GHz and " r = 8 at 13 GHz, with low firing temperatures of 900°C were found when the mixing ratio of La 2 O 3 -2B 2 O 3 -0.5ZnO was 20% crystalline melt and 80% amorphous melt. Kagata et al [92] reported MgO-Sm 2 O 3 -Al 2 O 3 (MgSmAl 11 O 19 ) and Al 2 O 3 -SiO 2 -B 2 O 3 in equal amount, and sintering at 920°C resulted in LTCC with " r = 7.8, Qf = 10 000 GHz and f = þ6 ppm/°C. Chang and Jean [93] studied the crystallization kinetics and mechanism of low " r , low temperature, cofireable CaO-B 2 O 3 -SiO 2 glass ceramics using commercially available A-6 tapes.…”
Section: Microwave Dielectric Properties Of Glassesmentioning
confidence: 99%